Haemoglobin Genetic types of some Major Gene types of Nigerian Indigenous Chicken (2012)
This study describe the genetic structure of the haemoglobin locus in frizzle and naked chickens of Nigerian indigenous chickens. 1 total of fifty-one birds comprising twenty-nine frizz and twenty-two naked neck birds were used for the study. The locus was polymorphic in the populations studied with genetic variants A and B. HbA had a frequency of 0.636 and <).65ifrizzle and naked neck respectively indicating the predominance of A in both populations. The l\codominant alleles control three haemoglobin genotypes AA. AB and BB. Genotype AA occult at the highest frequency in frizzle types while AB was the most frequent in naked neck birds. 7 populations were analyzed for genetic equilibrium based on the differences between II distributions. Both populations were in genetic equilibrium at the haemoglobin locus.